Uncertainty Characterization - Zhang, Jingxiong; Atkinson, Peter; Goodchild, Michael F. (Scale in Spatial Information and Analysis, 2014)
As mentioned toward the end of Chapter 11, uncertainty is inherent in spatial information and analysis. Uncertainty should thus be characterized properly. Although the information theory discussed in Chapter 11 provides a special language of reasoning in the face of uncertainty, this chapter addresses the topic of uncertainty characterization, in particular with respect to its relation to scale issues, the theme of this book.